2000
DOI: 10.4141/p99-098
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of foliar or soil application of 15N-labelled urea solution at anthesis and its affect on wheat grain yield and protein

Abstract: . 2000. Uptake of foliar or soil application of 15 N-labelled urea solution at anthesis and its affect on wheat grain yield and protein. Can. J. Plant Sci. 80: 331-334. Two growth chamber experiments were conducted to determine the effect of 15 N-labelled urea solution foliar-or soil-applied at anthesis on recovery of fertilizer N in grain, grain protein and grain yield of Canadian Western Red Spring wheat (Triticum aestivum L.). Recovery of 15 N-labelled urea-N in grain ranged from 4.5 to 26.7% with foliar ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
21
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 9 publications
1
21
1
1
Order By: Relevance
“…A positive relationship between N, provided by foliar fertilization at anthesis, and the bread-making quality of flour has been observed Tea et al, 2004). In greenhouse experiments, the recovery of 15 N-labeled N in wheat grain is generally higher for soil applications than foliar ones, although conflicting results have been observed on their capacity to increase the final GPC (Alkier et al, 1972;Rawluk et al, 2000). However, Gooding et al (2007) reported a higher recovery of N in grains in field experiments, after urea foliar application, compared to soil fertilization with ammonium nitrate.…”
mentioning
confidence: 87%
“…A positive relationship between N, provided by foliar fertilization at anthesis, and the bread-making quality of flour has been observed Tea et al, 2004). In greenhouse experiments, the recovery of 15 N-labeled N in wheat grain is generally higher for soil applications than foliar ones, although conflicting results have been observed on their capacity to increase the final GPC (Alkier et al, 1972;Rawluk et al, 2000). However, Gooding et al (2007) reported a higher recovery of N in grains in field experiments, after urea foliar application, compared to soil fertilization with ammonium nitrate.…”
mentioning
confidence: 87%
“…Application of post-emergence N has been successfully implemented on irrigated crops to manipulate grain protein content and, in some instances, grain yield (Hucklesby et al 1971;Goos et al 1982;Gravelle et al 1988;Stark and Tindall 1992;Tindall et al 1995). Under dryland conditions, post-emergence N applications have been primarily used in an attempt to influence grain protein (Grant and Flaten 1998;Rawluk et al 2000). The concentration of protein in wheat grain is influenced by the supply of nitrogen in the soil (Alkier et al 1972;Campbell et al 1977;Dubetz 1977;Campbell et al 1996;Selles and Zentner 1998) and its interaction with moisture and temperature (Partridge and Shaykewich 1972;Clarke et al 1990;Campbell et al 1997;Selles and Zetner 1998), cultivar (Fowler et al 1990;Gauer et al 1992) and timing of nitrogen application (Grant and Flaten 1998).…”
mentioning
confidence: 99%
“…Using a 15 N-labeling technique can help determine the recovery of foliar-applied N in wheat (Triticum aestivum L.) (Powlson et al 1989;Smith et al 1991;Rawluk et al 2002). Powlson et al (1989) reported that the recovery could be up to 70% through foliar application of N at anthesis in the aboveground parts including 64% in grains, whereas Rawluk et al (2000) recently reported that the recovery of foliar-applied N in wheat grain was much lower (5.5 to 26.7%) than that of soil-applied N (32.3 to 70.1%), and grain yield and protein were also higher for soil-applied than for foliar-applied N. Similarly, Readman et al (2002) observed a lower recovery of foliar-applied N than in the soil-applied treatment. Smith et al (1991) observed that grain N concentration increased with foliar N application and a greater increase in grain protein occurred when the application was close to flowering.…”
mentioning
confidence: 99%